2015
DOI: 10.1177/0267659115604710
|View full text |Cite
|
Sign up to set email alerts
|

Activated clotting time test alone is inadequate to optimize therapeutic heparin dosage adjustment during post-cardiopulmonary resuscitational extracorporeal membrane oxygenation (e-CPR)

Abstract: Our study demonstrates that the ACT test alone does not seem to be enough to optimize therapeutic heparin dosage adjustment during e-CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…6 Currently, ELSO guidelines recommend any combination of ACT, aPTT, anti-Xa, and TEG, but if ACT is selected, other tests should be used as a supplement given the shortcomings of ACT measurements in patients with anemia, hypofibrinogenemia, thrombocytopenia, coagulation factor deficiencies, dilution, and hypothermia. 23,24 Although the ELSO guidelines state that most centers that utilize anti-Xa protocols target 0.3 to 0.7 U/mL, based on our early experience with anti-Xa, our institution uses lower targets to try and minimize bleeding. This approach is consistent with the Sieg et al 19 data in which 2 heparin intensities were developed (anti-Xa 0.15-0.25 and anti-Xa 0.3-0.4) to mitigate bleeding in axillary Impella and percutaneous temporary LVAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Currently, ELSO guidelines recommend any combination of ACT, aPTT, anti-Xa, and TEG, but if ACT is selected, other tests should be used as a supplement given the shortcomings of ACT measurements in patients with anemia, hypofibrinogenemia, thrombocytopenia, coagulation factor deficiencies, dilution, and hypothermia. 23,24 Although the ELSO guidelines state that most centers that utilize anti-Xa protocols target 0.3 to 0.7 U/mL, based on our early experience with anti-Xa, our institution uses lower targets to try and minimize bleeding. This approach is consistent with the Sieg et al 19 data in which 2 heparin intensities were developed (anti-Xa 0.15-0.25 and anti-Xa 0.3-0.4) to mitigate bleeding in axillary Impella and percutaneous temporary LVAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, when viewing the large variety of tests used, it is not surprising that results are conflicting. While in some investigations a good correlation between both tests was found, a weak correlation was reported in some other investigations (19)(20)(21).…”
Section: Monitoring Of Anticoagulation With Ufhmentioning
confidence: 84%
“…These studies continue to demonstrate a poor correlation between the ACT and aPTT in patients receiving heparin on ECMO, 4-6 with 2 of them also indicating the superiority of the aPTT compared to the ACT with regard to the HID. 4,6 Another study demonstrated a poor correlation between the ACT and anti-factor Xa and a moderate correlation between the aPTT and anti-factor Xa level. 7 This important work confirms our opinion and validates our efforts in creating a multipronged approach using variables that may be more indicative of the efficacy of the HID.…”
Section: Authors' Responsementioning
confidence: 98%